Description of Brittle Damage in Concrete - Kubik, Jan; Perkowski, Zbigniew (Communications - Scientific letters of the University of Zilina, 2019)
A simple model of the brittle damage evolution in concrete is presented. The damage evolution is assumed as an isotropic one and the level of damages in material is described by the scalar parameter. The physical equations for this case are formulated.